Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.3390/medicina60050760
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress and Inflammatory Parameters in Heart Failure

Karolina Wróbel-Nowicka,
Celina Wojciechowska,
Wojciech Jacheć
et al.

Abstract: Heart failure (HF) remains a major medical and social problem. The NT-pro-brain natriuretic peptide (NT-proBNP) and its active form, brain-type natriuretic peptide (BNP), in a simple blood test are the gold-standard biomarkers for HF diagnosis. However, even good biomarkers such as natriuretic peptides fail to predict all the risks associated with HF due to the diversity of the mechanisms involved. The pathophysiology of HF is determined by numerous factors, including oxidative stress, inflammation, neuroendoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
0
0
0
Order By: Relevance
“…Overall, these findings underscore the importance of monitoring MDA levels as a marker for oxidative stress and its potential implications in biological systems (Bencivenga et al, 2023;Wróbel-Nowicka et al, 2024;Kong et al, 2024;Valavanidis et al, 2006). Further research may delve into elucidating the specific factors contributing to the observed increase in MDA levels in the control (+) group, leading to a better understanding of the underlying mechanisms and potential therapeutic interventions to mitigate oxidative stress-related damage.…”
Section: Figure 1 Mda Standard Curvementioning
confidence: 75%
“…Overall, these findings underscore the importance of monitoring MDA levels as a marker for oxidative stress and its potential implications in biological systems (Bencivenga et al, 2023;Wróbel-Nowicka et al, 2024;Kong et al, 2024;Valavanidis et al, 2006). Further research may delve into elucidating the specific factors contributing to the observed increase in MDA levels in the control (+) group, leading to a better understanding of the underlying mechanisms and potential therapeutic interventions to mitigate oxidative stress-related damage.…”
Section: Figure 1 Mda Standard Curvementioning
confidence: 75%